Risk analysis of climate change on coffee nematodes and leaf miner in Brazil - Ghini, Raquel; Hamada, Emília; Júnior, Mário José Pedro; Marengo, José Antonio; Gonçalves, Renata Ribeiro do Valle (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to assess the potential impact of climate change on the spatial distribution of coffee nematodes (races of Meloidogyne incognita) and leaf miner (Leucoptera coffeella), using a Geographic Information System. Assessment of the impacts of climate change on pest infestations and disease epidemics in crops is needed as a basis for revising management practices to minimize crop losses as climatic conditions shift. Future scenarios focused on the decades of the 2020's, 2050's, and 2080's (scenarios A2 and B2) were obtained from five General Circulation Models available on Data Distribution Centre from Intergovernmental Panel on Climate Change. Geographic distribution maps were prepared using models to predict the number of generations of the nematodes and leaf miner. Maps obtained in scenario A2 allowed prediction of an increased infestation of the nematode and of the pest, due to greater number of generations per month, than occurred under the climatological normal from 1961–1990. The number of generations also increased in the B2 scenario, but was lower than in the A2 scenario for both organisms.
Keywords: Coffea arabica; Leucoptera coffeella; Meloidogyne incognita; global warming; pest zoning